Teaching Methodology of Chemistry in Pedagogical Institutions of Higher Education - Muattarxon Tilavoldievna Akbarova (Euro Asian Journal Publishing, 2024)
This article discusses the ability to observe, explain, use knowledge and skills of chemical processes and phenomena, and solve various practical problems in the formation of chemical competence of non-specialist education students
Keywords: Chemical competence; chemistry major; higher education